Corien Wiersma. Building the Bronze Age: architectural and social change on the Greek mainland during Early Helladic III, Middle Helladic and Late Helladic I - Dakouri-Hild, Anastasia (Journal of Greek Archaeology, 2016)
This book, a revised doctoral dissertation undertaken at the University of Groningen, is a welcome study on the neglected topic of domestic architecture in the eras preceding the palatial civilization of the Greek Mainland (in particular the EH III-LH I span). It is structured very much as a dissertation: an introduction setting out the goals, justification and spatiotemporal framework of the study; a survey of prior research on the topic of Mainland domestic architecture (Chapter 1); a theory of domestic architecture, the household and the overall context within which it is nested (community, nearby settlements, regional), and the methodology used for the data underpinning the study (from selection and collection to processing and analysis; Chapter 2); an analytical presentation of architectural remains by region (Thessaly, Phocis and Phthiotis, Boeotia, Euboea, Attica, Corinthia, the Argolid, Laconia, Messenia, Elis, Arcadia and Achaia; Chapter 3); a synthesis of the architectural data by era (EH III, MH I-II, MH III-LH I; Chapter 4); an interpretative discussion of emerging patterns (on the regional, neighboring settlement, local community, individual household levels; Chapter 5); and a brief section presenting the conclusions (Chapter 6).